KEBIJAKAN NASIONAL PENGENDALIAN RABIES PADA MANUSIA - Mutazam Mutazam; Sri Asih Agustin; Poniam Poniam (JOURNAL OF COMMUNITY DEDICATION, 2023)
Rabies is an infectious disease caused by the rabies virus. Apart from that, rabies is also a disease of warm-blooded animals which can be transmitted to humans. The situation of rabies in Indonesia continues to increase every year from each province, until 2011 there were 52,503 cases of animal bites reported. Rabies transmitter, with 104 deaths due to rabies. Preventing the transmission of rabies can include vaccinating animals that transmit rabies, reporting any animals infected with rabies, and being alert to stray dogs. The aim of this research is to determine the behavior of dog owners towards preventing rabies.